2018
DOI: 10.1088/1361-6455/aae579
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz magnetic field enhancement in an asymmetric spiral metamaterial

Abstract: We use finite element simulations in both the frequency and the timedomain to study the terahertz resonance characteristics of a metamaterial (MM) comprising a spiral connected to a straight arm. The MM acts as a RLC circuit whose resonance frequency can be precisely tuned by varying the characteristic geometrical parameters of the spiral: inner and outer radius, width and number of turns. We provide a simple analytical model that uses these geometrical parameters as input to give accurate estimates of the res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…It will be permanently installed inside the THz beamline vacuum environment for distortionfree THz spectrum measurements, enabling quick and robust spectral studies [e.g. suitable for THz shaping by emerging THz meta-materials (Yen et al, 2004;Monticone & Alù , 2017;Stojanović et al, 2018;Polley et al, 2018)].…”
Section: Resultsmentioning
confidence: 99%
“…It will be permanently installed inside the THz beamline vacuum environment for distortionfree THz spectrum measurements, enabling quick and robust spectral studies [e.g. suitable for THz shaping by emerging THz meta-materials (Yen et al, 2004;Monticone & Alù , 2017;Stojanović et al, 2018;Polley et al, 2018)].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it has been shown that the MO activity of magnetoplasmonic structures can be enhanced by putting the MO active material at particular places within the structure [121,122]. On the other hand, metamaterials structures have shown their ability to design tailored electromagnetic fields in a very wide spectral range [123], and resonant meta-atoms with both plasmonic and (opto)-magnetic functionalities have shown great potential [124]. Therefore, exploring the use of metamaterials to maximize the electromagnetic field at the position of the spintronic component may be a way to further improve the performance of MRE based photonic platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Novel possibilities of optical control of magnetism on the nanometer scale via plasmonic resonances have emerged as well it was shown that femtosecond laser pulses [ 212 ] are able to generate magnons with nanometer wavelengths [213]. Moreover, intriguing new magnetic phenomena can be triggered in the THz region of the light spectrum [ 214 ], and fundamental efforts have been recently emerged in this direction to design metamaterials working in that frequency region to manipulate locally magnetic properties of matter [215,216]. Indeed, one of the missing pieces of this intricated puzzle is a systematic exploration of the fundamental properties of magneto-plasmonic metamaterials between the visible/near-infrared and the THz regions.…”
Section: Discussionmentioning
confidence: 99%